2019
DOI: 10.3390/f10121056
|View full text |Cite
|
Sign up to set email alerts
|

Forestry Policy, Conservation Activities, and Ecosystem Services in the Remote Misuku Hills of Malawi

Abstract: Research Highlights: Most of Malawi's land area has been deforested; however, expansive indigenous forests remain in the remote Misuku Hills in Malawi's northern region. Despite its conservation potential, this region of Malawi has been overlooked in forestry conservation research. Background and Objectives: The Misuku Hills is one the most floristically diverse regions in Malawi, but this region is facing similar pressures and forestry policy enforcement challenges that drive deforestation of other regions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Lack of access to skills and institutions meant that local institutions could not provide the platform for learning and developing skills and attitude in areas beyond the forestry sector (Coutts et al, 2019;Hinchcliffe et al, 1996). Therefore, proper application of the SLA process at the beginning of IFMSLP, would have determined the roles that forest resources could have played in meeting basic needs.…”
Section: Discussion Realization Of Basic Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of access to skills and institutions meant that local institutions could not provide the platform for learning and developing skills and attitude in areas beyond the forestry sector (Coutts et al, 2019;Hinchcliffe et al, 1996). Therefore, proper application of the SLA process at the beginning of IFMSLP, would have determined the roles that forest resources could have played in meeting basic needs.…”
Section: Discussion Realization Of Basic Needsmentioning
confidence: 99%
“…The majority of the population (84%) live in the rural area where income generation opportunities are low. The land holding size per household is small (0.5-2 ha) as such the people extract natural resources in their immediate environment for daily household use and income generation (Coutts et al, 2019).…”
Section: Study Area Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there is a high rate of unemployment in Malawi and this was expected to be exacerbated by the pandemic, with an estimated loss in jobs at about 3% as a result of the pandemic (International Labour Organization, ILO, 2020). Consequently, high unemployment will invariably lead to a fall back in the direct extraction of forest resources from the immediate environment for daily household use and to sell for profit (Coutts et al, 2019). This is because forests provide food, fuelwood, medicine, timber, employment and other non-timber products (NTFPs) that can sustain wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…In the Misuku Hills in Malawi, for example, a variety of policies have been adopted following international standards to increase local control and promote community-based management in forests. Despite the lack of implementation and enforcement of the proposed policies, forest conservation activities (e.g., enhancing tree planting and natural regeneration, forest protection at a catchment scale to conserve biological and cultural diversity, forest resources extraction regulation, promotion of beekeeping) indicate that rural communities have the potential to take over the management of customary and public forest lands [8]. In Tanzania, Gizachew et al [9] found that most PAs were effective in reducing deforestation rates, even if there were important pressures in their surrounding lands.…”
mentioning
confidence: 99%